2021
DOI: 10.1038/s42003-021-02380-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive divergence and post-zygotic barriers to gene flow between sympatric populations of a herbivorous mite

Abstract: Plant-herbivore interactions promote the generation and maintenance of both plant and herbivore biodiversity. The antagonistic interactions between plants and herbivores lead to host race formation: the evolution of herbivore types specializing on different plant species, with restricted gene flow between them. Understanding how ecological specialization promotes host race formation usually depends on artificial approaches, using laboratory experiments on populations associated with agricultural crops. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 99 publications
4
42
1
Order By: Relevance
“…Among the five strains, variant prediction revealed 1.19 million high-quality variants (SNPs and small indels), consistent with prior studies that have revealed substantial variation among T. urticae strains [51][52][53][54]. Further, more than 98% of SNP sites were fixed in each of the five strains, confirming earlier reports that ~7 generations of inbreeding in this haplodiploid species results in isogenic (or nearly isogenic) strains [52].…”
Section: Five Inbred Strains Harbor Extensive Genetic Variationsupporting
confidence: 88%
See 4 more Smart Citations
“…Among the five strains, variant prediction revealed 1.19 million high-quality variants (SNPs and small indels), consistent with prior studies that have revealed substantial variation among T. urticae strains [51][52][53][54]. Further, more than 98% of SNP sites were fixed in each of the five strains, confirming earlier reports that ~7 generations of inbreeding in this haplodiploid species results in isogenic (or nearly isogenic) strains [52].…”
Section: Five Inbred Strains Harbor Extensive Genetic Variationsupporting
confidence: 88%
“…urticae strains [51][52][53][54]. Further, more than 98% of SNP sites were fixed in each of the five strains, confirming earlier reports that ~7 generations of inbreeding in this haplodiploid species results in isogenic (or nearly isogenic) strains [52].…”
Section: Five Inbred Strains Harbor Extensive Genetic Variationsupporting
confidence: 86%
See 3 more Smart Citations